Illegal Factories in Mukim Parit Bakar, Muar: Implications to Residential Properties - Tay Yie Jie,; Burhan, Burhaida (Research in Management of Technology and Business, 2020)
In Malaysia, generally under the National Land Code 1965, land use can be divided into three categories, which are building, agriculture and industrial. Non-compliance of land use such as misuse of residential or agricultural land for industrial activity would bring problems to the residents in the vicinity. In Parit Bakar, Muar, Johor there are a number of illegal factories that operate on agricultural land that is not gazetted for industrial activities. It is a common belief that the existence of industrial activity nearby would cause environmental pollution and lower the demand and property price of that surrounding area. Hence, objectives of this research are to study the effects of the existence of illegal factories towards the housing price and to study the relationship of illegal factories location and housing distribution in Mukim Parit Bakar. The objective of this study is achieved by using Multiple Regression Analysis (MRA) and distance analysis. Transaction data of residential properties in the research area provided by the Valuation and Property Service Department (JPPH) Muar were analyzed using Statistical Package for the Social Science (SPSS) software. MRA results indicated that distance to illegal factories significantly affect the property price in the surrounding area and the relationship between housing price and illegal factories varies geographically in a positive and negative way. Distance to illegal factories, which are located at the center region, has a positive impact on housing price and thus give benefit to housing schemes nearby.